TERRITORIAL COMPETITIVENESS IN THE ECONOMIC DECENTRALIZATION OF PERU - Andaluz Westreicher, Tarcisio (2017)
Decentralization, state and government policy; it is also the convergence of discourses of any ideological tendency; its territorial expression: regions and municipalities; the trend, reduce the number of regions as panacea; its administrative expression, functional and sectoral decentralization; its fiscal expression, tax and monetary transfers; the problem, that for fifteen years of decentralist practice and ninety years of theorization, since Mariategui, none of its expressions were manifested in a modification of the productive structure, in economic decentralization and in territorial competitiveness; despite the greater autonomy granted. Meanwhile, globalization needs authonomy and democracy to legitimize sovereign decisions and unite differences in North – South, center- peripheries. The procedure: collection of theoretical, legal, institutional and comparative data; confronted with the actual news. The results: globalization as a union of poles and differences; competitiveness, a centralist and centralizing concept that only finds a rival in Meyer-Stamer’s concept of systemic competitiveness. The global tendency to enlarge territories in regions, against the reductionist historical tendency; decentralization through fiscal discipline increased the deinstitutionalization of the state; the distributive decentralization of lands, money and functions without economic decentralization is to put the cart before the horses and a remedy worse than the disease.